Educational Innovation in Spain: A Focus Group approach - Sánchez Moreno, Marita; Murillo Estepa, Paulino (Profesorado, Revista de Currículum y Formación del Profesorado, 2010)
This paper presents part of the results obtained from a broader study proposed by CIDE (Centro de Investigación y Documentación Educativa). The results of the quantitative analysis from CIDE study are also set out in another article of this special issue. The basic aim of that investigation was to inquire into educational innovations processes in the Spanish context. Specifically, the conditions which enable and constrain the planning, implementation and evaluation of educative innovations were analyzed, as well as the features and processes carried out in schools which develop them and the results obtained. The findings in this article correspond to the information collected by means of the qualitative processes used in the investigation. The conclusions support the quantitative data obtained and explain the features declared by those involved in educational innovations in Spain.